Аnalysis of the effectiveness of countermeasures to protect the ecosystems on slopes landscapes using box models - Петрусенко, В.П.; Кутлахмедов, Ю.О. (Proceedings of National Aviation University, 2006)
For the analysis of efficiency of counter-measures on defence of ecosystems from radioactive contamination is created block-scheme of slope`s ecosystem. The design of processes of migration of radionuclides in slope`s ecosystems is conducted by the method of box models with the use of counter-measures. The results of design allow to estimate and choose the optimum algorithm of choice of counter-measures.